«Raucana, caught between fear and hope (1990-2000)»: The attitudes of the sectors and their relationship with the Communist Party of Peru - Shining Path, in the district of Ate - Rojas Rivera, Luis Arturo (2022)
The main objective of this article is to analyze the attitudes during the Internal Armed Conflict of the residents of Raucana, a community located in the district of Ate, belonging to the Eastern Cone of metropolitan Lima. To do this, in this article I discuss how this “support base” community, generated by the organizational apparatus of the Communist Party of Peru-Sendero Luminoso, developed various attitudes towards the presence and predominance of Shining Path, which translated into an initial acceptance, ambiguity or indifference to later mutate into a rejection of Sendero and, finally, into the acceptance of the new order with the intervention of the Army, and the development of state patronage.